LEGALITAS IZIN USAHA PERTAMBANGAN KHUSUS OPERASI PRODUKSI PT. FREEPORT INDONESIA - Amri Nur Azizah (Universitas Halu Oleo, 2020)
This legal research aims to review and analyze to the legality of the Special Mining Business Permit (known as IUPK) of PT. Freeport Indonesia (PT. FI). The research method uses a statute, conceptual and case approach. The legal material used in this research was obtained from the legislation, legal principles, legal concepts, and doctrines related to the legality of the Special Mining Business Permit (IUPK) of PT. Freeport Indonesia as a source of primary material as well as literature (including journals both national and international journals), articles, internet, and scientific papers, contains developments or actual issues regarding the law of certain fields as secondary legal material. The results of this study to explain that the Special Mining Business Permit (IUPK)of PT. FI is the result of an agreement made by the Indonesian government and PT. FI. The Special Mining Business Permit (known as IUPK) of PT. Freeport Indonesia (PT. FI) is contrary to the requirements and procedures established based on Law Number 4 of 2009 on Mineral and Coal Resources (the Minning Law).